2003
DOI: 10.1021/ja0346375
|View full text |Cite
|
Sign up to set email alerts
|

Metallocene Polymerization Catalyst Ion-Pair Aggregation by Cryoscopy and Pulsed Field Gradient Spin−Echo NMR Diffusion Measurements

Abstract: Pulsed field gradient spin-echo (PGSE) NMR and cryoscopic measurements have been performed on a series of homogeneous metallocene polymerization catalyst ion-pairs to determine if aggregation is a significant phenomenon under typical polymerization conditions. Cryoscopic measurements on [(Me5Cp)2ZrMe]+[MeB(C6F5)3]- (1), [rac-Et(Indenyl)2ZrMe]+[MeB(C6F5)3]- (2), [(1,2-Me2Cp)2ZrCHTMS2]+[MeB(C6F5)3]- (3), [Me2Si(Me4Cp)(t-BuN)TiMe]+[MeB(C6F5)3]- (4), [Me2Si(Me4Cp)(t-BuN)ZrMe]+[MeB(C6F5)3]- (5), and [Me2C(Fluorenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 24 publications
7
54
0
2
Order By: Relevance
“…8 (2) and 2.1100(2) Å] due to the increased metal electrophilic character, whereas the Ti-Me(bridging) separation is 0.230 Å longer, reflecting the largely ionic character of the ion pair interaction. NMR spectroscopy reveals characteristic fingerprints of a very coordinatively unsaturated, electrophilic metal center, as well as strong but coordinatively flexible ion pairing and negligible ion pair aggregation in the concentration ranges used for typical polymerization (23,24).…”
Section: Binuclear Perfluorophenyl Bisborane and Bisborate Cocatalystmentioning
confidence: 99%
“…8 (2) and 2.1100(2) Å] due to the increased metal electrophilic character, whereas the Ti-Me(bridging) separation is 0.230 Å longer, reflecting the largely ionic character of the ion pair interaction. NMR spectroscopy reveals characteristic fingerprints of a very coordinatively unsaturated, electrophilic metal center, as well as strong but coordinatively flexible ion pairing and negligible ion pair aggregation in the concentration ranges used for typical polymerization (23,24).…”
Section: Binuclear Perfluorophenyl Bisborane and Bisborate Cocatalystmentioning
confidence: 99%
“…[7] Normally, one does not find an explanation for the effect of the anion; however, occasionally, ion pairing is mentioned as a possible contributor. [11,17] It is not always evident how one should measure and recognize this ion pairing; however, recent NMR studies, which combine both pulsed gradient spin-echo (PGSE) diffusion and Overhauser NMR spectroscopy, [14,15] , have begun to shed light on how selected anions interact with their respective cations in solution. Usually, the literature studies involving NMR diffusion measurements emphasize the use of this methodology in connection with recognizing changes in molecular volumes.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Nevertheless, one finds an increasing number of reports involving NMR data and ion pairing. [15,17,[31][32][33] Assuming that the two ions can be measured separately, inspection of the magnitudes of the NMR diffusion constants provides a direct estimate of the extent of the Abstract: PGSE diffusion, 19 F, 1 H HOESY and 13 À salts of transitionmetal, inorganic, and organic salts are compared. Taken together, these new results show that the charge distribution and the ability of the anion to approach the positively charged positions (steric effects due to molecular shape)…”
Section: Introductionmentioning
confidence: 99%
“…Indeed in some cases, it has been shown that a molecule of solvent would rather bind to the vacant site of the cation than [BF 20 ] -; this is a testament to the anion's non-coordinating nature [133][134][135] -can interact with cations sufficiently to form higher aggregates [137]. Marks et al [138] reported using similar PGSE NMR measurements in C 6 [121,122] quadruples or even hextuples in solution at higher concentrations. It is worth noting that the previously mentioned PGSE NMR experiments were carried out at concentrations above that which is usually used in single-site catalysis, and the existence of these aggregates at lower, more relevant, concentrations is more unlikely.…”
Section: Anion and Solvent Interactionsmentioning
confidence: 99%